Faktor–Faktor Yang Berhubungan Dengan Pemberian ASI Eksklusif Pada Ibu Bekerja di Kelurahan Cipare Kota Serang - Nila Marwiyah; Titi Khaerawati (Faletehan Health Journal, 2020)
Infant and child mortality rates may be caused by not getting exclusive breastfeeding. One of the factors of inadequate breastfeeding is mothers' difficulty in breastfeeding, especially working moms. The purpose of this research is to identify factors related to exclusive breastfeeding among working moms in Cipare Village at Work Area of Serang City Community Health Center. The research design is cross-sectional. The sampling technique is purposive sampling with 51 respondents. The univariate data analysis was presented by frequency distribution, while the bivariate analysis by chi-square. The univariate analysis showed that almost all respondents did not give exclusive breastfeeding and almost all respondents got support from their boss. The results of the bivariate analysis showed a correlation between exclusive breastfeeding and parity status (p-value 0.011), education background (p-value 0.037), knowledge (p-value 0.035), family support (p-value 0.006), and boss support (p-value 0.006). The understanding of the importance of exclusive breastfeeding helps working moms breastfeed for 6 months. The research results may be a basis for evaluating working moms to optimize the use of lactation rooms and to keep exclusive breastfeeding for their babies.